Pengembangan Multimedia Interaktif untuk Meningkatkan Kecerdasan Visuospasial Siswa SMA Melalui Strategi Three-Tier Test - Kusumawati Dwiningsih; Ryo Widi Danielson; Vivi Damayanti; Putri Kurnia Lestari (Jurnal Paedagogy, 2023)
This study aims to develop interactive multimedia to improve high school students' visuospatial intelligence in the oxidation state's redox reaction material through a three-tier test strategy. This research used the ADDIE development method, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The research subjects were students at one of the high schools in Gresik Regency. The research instruments used were visuospatial intelligence test sheets, interactive multimedia validation questionnaires, and practicality questionnaires. Posttest results were analyzed based on normality, homogeneity, and N-gain. The results of this study indicated that the developed interactive multimedia could improve students' visuospatial intelligence. It was based on the results of validation and limited trials obtained from the aspect of validity assessment with a score of 84% and got the title very valid. Then practicality got the title very practical with a score of 91%. Effectiveness could be seen from students' pretest and posttest scores, with the normality test for the pretest score getting a score of 0.191 while the posttest got a score of 0.220 so that it is normally distributed. The T test got a score of <0.05, which Ha accepted. The N-Gain test got a score of 0.89, with a high rating.